Dietary advanced glycation end-products and postmenopausal hot flashes: A post-hoc analysis of a 12-week randomized clinical trial. (June 2023) - Kahleova, Hana; Znayenko-Miller, Tatiana; Uribarri, Jaime; Schmidt, Natalie; Kolipaka, Sinjana; Hata, Ellen; Holtz, Danielle N.; Sutton, Macy; Holubkov, Richard; Barnard, Neal D.
Highlights: This study examined the potential association of modifications to the intake of dietary advanced glycation end-products (AGEs) with the frequency and severity of postmenopausal hot flashes. Severe hot flashes decreased by 92% ( p <0.001) and moderate-to-severe hot flashes decreased by 88% in the intervention group ( p <0.001). Dietary AGEs decreased in the intervention group by 73%, that is by 5, 509 ku/day on average (95% -7, 009 to -4, 009; p<0.001), compared with the control group (+458; 95% CI -835 to +1751; p =0.47; treatment effect -5, 968 ku/day [95% CI -7945 to -3991]; Gxt, p <0.001). Changes in dietary AGEs correlated with changes in severe (r=+0.39; p =0.002) and moderate hot flashes (r=+0.34; p =0.009) and remained significant after adjustment for changes in energy intake (r=+0.45; p<0.001; and r=+0.37; p =0.004, respectively) and changes in body mass index (r=+0.37; p=0.004; and r=+0.27; p =0.04, respectively). The reduction in dietary AGEs required to achieve a predicted reduction in hot flashes by 1/day was 6, 933 ku/day for severe and 4, 366 ku/day for moderate-to-severe hot flashes. Due to the beneficial effects, plant-based diets could be used to alleviate vasomotor symptoms in postmenopausal women. Abstract: Objective: Postmenopausal hot flashes are associated with an increased risk of cardiovascular disease and diabetes. Because dietary advanced glycation end-products (AGEs) may act as endocrine disruptors, this study examined the potential association of modifications to the intake of dietary AGEs with the frequency and severity of postmenopausal hot flashes. Methods: Postmenopausal women ( n = 84) reporting ≥2 moderate-to-severe hot flashes daily were randomly assigned to either the intervention group or the control group. The former were asked to follow a low-fat, vegan diet, including cooked soybeans (1/2 cup [86 g]/day) for 12 weeks, and the latter continued their usual diets for 12 weeks. Frequency and severity of hot flashes were recorded with a mobile application. Three-day diet records were analyzed using the Nutrition Data System for Research software and dietary AGEs were estimated, using a database. Seventy-one participants completed the whole study and 63 provided complete hot flash and dietary data for the AGEs analysis ( n = 31 in the intervention and n = 24 in the control group). Pearson correlations were used to assess the association between changes in hot flashes and dietary AGEs. Results: Dietary AGEs decreased in the intervention group by 73 %, that is by 5509 ku/day on average (95 % −7009 to −4009; p < 0.001), compared with the control group (+458; 95 % CI −835 to +1751; p = 0.47; treatment effect −5968 ku/day [95 % CI −7945 to −3991]; Gxt, p < 0.001). Severe hot flashes decreased by 92 % (p < 0.001) and moderate-to-severe hot flashes decreased by 88 % in the intervention group (p < 0.001). Changes in dietary AGEs correlated with changes in severe (r = +0.39; p = 0.002) and moderate hot flashes (r = +0.34; p = 0.009) and remained significant after adjustment for changes in energy intake (r = +0.45; p < 0.001; and r = +0.37; p = 0.004, respectively) and changes in body mass index (r = +0.37; p = 0.004; and r = +0.27; p = 0.04, respectively). The reduction in dietary AGEs required to achieve a predicted reduction in hot flashes by 1/day was 6933 ku/day for severe and 4366 ku/day for moderate-to-severe hot flashes. Conclusions: The reduction in dietary AGEs with a low-fat plant-based diet was associated with a significant reduction in the frequency of severe and moderate-to-severe postmenopausal hot flashes, independent of changes in energy intake and weight loss. Plant-based diets could be used not only to alleviate vasomotor symptoms in postmenopausal women, but also to reduce other health risks associated with AGEs. Trial registration: ClinicalTrials.gov, NCT04587154 .